THE INFLUENCE OF LEADERSHIP CHARACTERISTICS AND WORK ENVIRONMENT ON EMPLOYEE WORK PERFORMANCE AT THE KALIWATES DISTRICT OFFICE - Hadiatullah, Deni (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the influence of leadership characteristics and the work environment on employee performance at the Kecamatan Kaliwates office. Effective leadership is often regarded as a pivotal element in shaping organizational outcomes, as it directly impacts employee motivation, satisfaction, and productivity. Concurrently, the work environment plays a significant role in fostering or impeding employee performance. Method: Utilizing a quantitative research approach, this study will collect data from employees to assess the relationships between leadership traits, work environment factors, and employee performance. By employing statistical analysis techniques, we aim to determine the extent to which these variables interact and contribute to overall employee effectiveness. Results: The findings of this research are anticipated to provide essential insights for policymakers and managers within the public sector, particularly in enhancing leadership practices and optimizing work environments to improve employee performance. Novelty: This study contributes to the existing literature by emphasizing the importance of both leadership and environmental factors in the context of public service organizations.